Vztah agrárního politika Františka Udržala k existenci Rakouska-Uherska v letech 1914-1917 - Charbuský, Miloš (Univerzita Pardubice, 2001)
Conditions for František Udržal political activities were substantionally changed since the beginning of the First World War. The Vienna parliament where he defended interests of the Agrarian Party as well as the Czech national mowement as the whole was closed already in the 15th January 1914. Although the persecution of the Czech nation made by the Austrian-Hungarian state was streghtened František Udržal did not join the resistant movement developed in abroad. He did not emigrated nor he did not become the T. G. Masaryk, E. Beneš and M. R. Štefanik co-worker. František Udržal together with the leadership of the Agrarian Party came out from the persuption that Austrian-Hungarian Empire supported by its stronger ally - Germany - would achieve the victory in the war conflict. His position started to be changed only since 1917 year. He quite openly resiste to the idea that the Czech state should become the competent part of Habsburg Central European monarchy during the parliamentary autumn meeting in 1917.
Keywords: Udržal, František; agrární politika; Rakousko-Uhersko; 1914-1917